Process Design for Tough Ductile Martensitic Steels through Direct Quenching and Partitioning. (2015) - Somani, M.C.; Porter, D.A.; Karjalainen, L.P.; Suikkanen, P.P.; Misra, R.D.K.
Abstract: A novel processing route comprising of thermomechanical rolling followed by direct quenching and partitioning (DQP) has been established for developing tough ductile high strength steels with yield strengths ≈1100 MPa. Suitable compositions were designed based on high silicon and/or aluminum contents and the microstructural mechanisms and DQP parameters established through physical simulation on a Gleeble simulator. Based on these results, suitable laboratory rolling trials were designed that also enabled coiling simulation. Desired martensite-austenite microstructures in respect of refined and randomized martensite packets/laths and finely divided austenite resulted in excellent mechanical properties, particularly at low quenching temperatures.